Oncoprotein Cot1 Represses Kinase Suppressors of Ras1/2 and 1,25-Dihydroxyvitamin D(3)-Induced Differentiation of Human Acute Myeloid Leukemia Cells - WANG, XUENING (2011)
Metabolites and derivatives of vitamin D are well-known inducers of monocytic differentiation, but the mechanistic basis for their action is not fully elucidated. Here we show that the product of protooncogene Cot1 represses the monocytic phenotype in human acute myeloid leukemia (AML) cells induced to differentiate by 1,25-dihydroxyvitamin D(3) (1,25D), even though the expression of cellular Cot1 increases early in the process of 1,25D-induced differentiation. Interestingly, the expression of the two members of the Kinase Suppressor of Ras (KSR) family of molecular scaffolds, known to be positive regulators of Ras signaling and of 1,25D-induced differentiation, increases in parallel with Cot1 in 1,25D-treated cells. However, KSR1/2 are negatively regulated by Cot1, as determined by transfection of siCot1, and confirmed by a reverse effect of ectopic expression of Cot1. The effect of Cot1 in AML cells appears to be cell-type specific, as previous reports in other cell types found KSR-2 to be a negative regulator of Cot1, a reverse relationship. Also in contrast to findings in other cells, in AML cells Cot1 exerts negative control on the MAP kinase pathways, since siCot1 increases the levels of activated Raf1, p90RSK, JNK1, c-jun, and p38, though not of MEK/ERK. These findings have implications for therapy of AML, since in AML cells active MAPKs hasten cell differentiation, and specific pharmacological inhibitors of Cot1 kinase activity have recently became available, thus making Cot1 a “druggable” target.